2013
DOI: 10.1294/jes.24.17
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C Expression in Equine Tendon-derived Cells During Proliferation and Migration

Abstract: In vitro cell studies might be a useful tool for studying tendon pathology, but no suitable in vitro models exist for tendon disorders. The purpose of this study was to confirm whether cell scratch culture using tendon-derived fibroblasts can provide a suitable in vitro tendon disorder model. Extracellular matrix components were examined immunohistochemically in tendon tissue, and then their related gene expression levels were analyzed by conventional reverse transcription polymerase chain reaction (RT-PCR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…One of the tendon markers assessed was TNC , a disulfide‐linked hexamer glycoprotein and member of ECM proteoglycans (Xu et al, ) suggested to be involved in the regulation of tendon formation (Smith, Zunino, Webbon, & Heinegård, ) and repair (Nemoto, Kizaki, Yamamoto, Oonuma, & Hashizume, ). Low levels of TNC expression in tenocytes isolated from healthy adult tissue is one of the features of tensional tendon phenotype (Taylor et al, ) that combined with a high expression of COL 1 and SCX are most representative of the normal adult tendon phenotype (Taylor et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the tendon markers assessed was TNC , a disulfide‐linked hexamer glycoprotein and member of ECM proteoglycans (Xu et al, ) suggested to be involved in the regulation of tendon formation (Smith, Zunino, Webbon, & Heinegård, ) and repair (Nemoto, Kizaki, Yamamoto, Oonuma, & Hashizume, ). Low levels of TNC expression in tenocytes isolated from healthy adult tissue is one of the features of tensional tendon phenotype (Taylor et al, ) that combined with a high expression of COL 1 and SCX are most representative of the normal adult tendon phenotype (Taylor et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…All patients granted informed consent. Tendon fragments were subjected to mechanical dissociation, and maintained in Dulbecco’s Modified Eagle Medium (DMEM) containing 1% antibiotics plus 10% Fetal Bovine Serum (FBS; Nemoto et al, 2013 ); 0.25 mM L-ascorbic acid was added to the medium to allow COLVI tetramer secretion (Engvall et al, 1986 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tenocytes, the mature cell type of the tendon, have a low proliferative capacity, thus, cultured tendon cells mainly derive from progenitor cells, which display a fibroblast-like phenotype [19]. We used "tendon fibroblasts" to indicate tendon-derived cultures.…”
Section: Tendon Cell Culturesmentioning
confidence: 99%